Low enrolment pattern into physical and health education course: osun state colleges of education as a case study (2008)
Physical education refers to the process of education that concerns activities which develop and maintain human body. It is an important part of the educational process that its evaluation as a teaching subject has developed tremendously. However, more students in the past were more than eager to pursue the course at a higher degree level that at the undergraduate level. But unfortunately physical education student enrolment in the Universities and Colleges of Education bos declined dramatically. This study therefore investigate the factor heading to low enrolment pattern into Physical and Health Education course in the two Osun State Colleges of Education. The population for this study consisted of all two hundred and fifty (250) respondents who were selected through quota sampling technique from the five schools making up the colleges. A structured questionnaire was used for data collection. Descriptive statistics was used to analyse the demographic characteristics and multiple regression on statistics set at 0.05 alpha level was used to test the hypotheses. The study showed that misconception about physical education and it double major status are among the reason of low enrolment into PHE ' departments in the two colleges. The findings were discussed in the light of the need to make physical education on fit into the dominant teaching subjects not only in the sciences but also in the area of social sciences/vocational and technical education